Pengembangan Bahan Ajar Berbasis Budaya Lokal Materi Keragaman Budaya Di Indonesia Pada Mata Pelajaran IPAS - Dwi Oktaviana; Atim Rinawati (IAINU Kebumen, 2026)
The aims of this research are (1) to describe the development of culture-based teaching materials on the material of Cultural Diversity in Indonesia, (2) to determine the feasibility of local culture-based teaching materials on the material of Cultural Diversity in Indonesia, (3) to determine the responses of educators and students to local culture-based teaching materials on the material of Cultural Diversity in Indonesia. This research is a Research and Development (R&D) study with a 4-D (four D) development model. The steps taken by the researcher are 1) the definition stage, 2) the design stage, 3) the development stage, 4) the dissemination stage. Data collection techniques were carried out through observation and questionnaires with a Likert scale for responses. Validation was carried out by material experts and media experts as well as the results of the trial responses of educators and students. The developed teaching materials were tested on 21 fourth-grade students at Wonotirto 1 Elementary School. Based on data analysis, it shows that culture-based teaching materials “Booklet” are feasible and interesting to use in learning cultural diversity in Indonesia. Keywords: Teaching Materials, Booklet, Local Culture